Deciphering the Notch Pathway: A Bioinformatics Analysis of the RBPJ/Notch Axis - Friedrich, Tobias; Justus Liebig University Giessen (My University, 2023)
Notch-mediated signal transduction plays a pivotal role for multiple biological processes in development, differentiation and cell homeostasis. Its dysregulation has been linked to several diseases, including different types of cancer. RBPJ is the central transcription factor in Notch signaling, which functions as a molecular switch acting either as an activator or a repressor depending on the activation state of Notch signaling. The RBPJ/Notch complex recruits different co-factors influencing the adjacent chromatin structure and thereby controls transcription. The transcriptional outcome of the Notch pathway is highly context-dependent and therefore difficult to define. In addition, the repressive function of RBPJ and the role of RBPJ in chromatin regulation and signaling dynamics still remain enigmatic. In this study, transcriptomics and epigenomics approaches were used to characterize both the repressive and activating function of RBPJ. Surprisingly, only a small subset of RBPJ sites act as repressors or activators of Notch target genes and can alter chromatin structure accordingly. I was able to show that RBPJ does not appear to act as a repressor and activator of all Notch target genes equally, rather there are distinct clusters of RBPJ/Notch-mediated transcriptional responses. These Notch-dependent or Notch-independent clusters are associated with distinct biological functions. Furthermore, the responsive RBPJ sites are characterized by comparable features like genomic location and binding strength. Strikingly, these features turned out to be evolutionary conserved, cell-type independent and allowed to computationally predict the responsiveness of RBPJ sites using only RBPJ ChIP-seq data in several cellular models. Taken together, my studies of the repressive and activating functions of RBPJ provide a redefined model for the transcriptional response mediated by Notch. Ultimately, this leads to a better understanding of distinct functions of RBPJ and a more accurate identification of Notch target genes. It is likely that the rules for Notch responsiveness and RBPJ binding, or at least comparable ones, are valid to be applied for several other inducible systems and their corresponding transcription factors.
Keywords: Bioinforamtics; RBPJ; Notch Pathway; ddc:570; ddc:610